Gender Differences in Adherence to Mediterranean Diet and Risk of Atrial Fibrillation. - Mattioli, A.V; Sonia, Pennella; Pedrazzi, P; Farinetti, A (Journal of Hypertension and Cardiology, 2015)
Background. Adherence to the Mediterranean Diet (MedD) is associated with a reduction of overall mortality and mortality from cardiovascular diseases and cancer. In a previous study we found a relationship between intake of antioxidant vitamins with diet and risk of atrial fibrillation (AF). The present study focuses on gender differences relative to diet and antioxidant intake in patients (pts) with a first detected episode of AF. Methods. A group of 400 pts, 205 men and 195 women, was investigated. A control group of 400 subjects, age and sex matched, was selected and compared. Nutritional parameters were assessed by a self-administered food frequency validated questionnaire (116 items) completed by an interviewer-administered 24 h diet recall. We previously constructed a MedD adherence score based on a prior scoring system developed for the Greek population. Consumption of cereals, vegetables, legumes, fruit, fish, dairy products, cups of espresso coffee, chocolate snacks, soda drinks and wine was investigated. Results. The MedD Score was higher in women compared to men (28.8 + 2.0 vs 20.1 + 2.5; p<0.001) and was higher in healthy subjects compared to patients with AF (27.9 + 5.6 vs 22.3 + 3.1; p<0.001). In pts with AF the estimated intake of total antioxidants was higher in women (19.9 ± 5.6 vs 11.2 ± 7.4 mmol/d; p<0.001), and women had higher intake of antioxidants from fruit and vegetables. Conclusions. Women showed high adherence to the MedD and higher intake of antioxidants from fruit and vegetables compared to AF men. Men had higher intake of antioxidants from coffee. Women that developed AF were older, with lower adherence to the MedD, and were more sedentary.
Keywords: Mediterranean diet; atrial fibrillation; antioxidants; gender.